PENGENDALIAN PIUTANG YANG EFEKTIF DALAM USAHA MENINGKATKAN PERPUTARAN PIUTANG PT. HERVITAMA INDONESIA - Andriyani, Fifin (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
This study aims to control effectively the accounts receivable to increase the companys receivables turnover. The analysis used is the analysis of the ratio , accounts receivable turnover analysis and analysis of the billing period. Based on the companys credit policy determination of repayment period is 30 days . The company does not yet have syarat-syarat/ketentuan credit sales . The implementation of the companys credit policies based only instruction directors in an effort to fulfill sales targets ( turnover ) . Year 2010 for doubtful accounts of Rp . 58,345,295 . The company implemented a backup method of allowance for doubtful accounts . Investment Analysis Everage in 2010 the company showed the amount of money invested in a single receivable turnover is quite high . This is because the average length of the repayment of the past due receivables . Analysis of the companys liquidity ratio in 2010 showed 120 % of the current ratio , cash ratio of 0.7 % at , and quick ratio at 116 % .Keywords: Credit Policy , Control Accounts Receivable , Cash Flow Effectiveness .